Some Biochemical Tests of Broiler Chickens As Affected by Different Levels of Sodium Bicarbonate - Kadhim S. Kadhim (Journal of Global Pharma Technology, 2017)
The objective of this research to investigate the effect of supplementation of sodium bicarbonate on some biochemical parameters of broiler chickens. At 42 day-old, broiler chickens were randomly allotted to three dietary treatments, 50 chickes in each fed on diet contain (0%, 0.5% and 1%) of sodium bicarbonate. Then each group was divided in to sub groups, 25 animals in each. At day 42 (the end of the experimental period), chickes were given 5h fasting period and blood plasma of chicks were collected without anticoagulant and plasma were separated by centrifugation at 3000 rpm for ten minutes and stored in a deep freez (-20) until analysis serum Carietenini , HDL , Globulins , ALP , ALT , AST , cholesterol , Glucose and total protein were determined by full auto biochemistry technique . As a result , in broiler chickens supplementation of different levels of sodium bicarbonate caused important changes in some biochemical parameters .Significantly positive correlations (P ≤ 0.01) were detected for HDL , ALP , ALT ,and AST , while (P ≤ 0.05 ) for Glucose and total protein . It seems, different levels of sodium bicarbonate were no Significant effect on blood Carietenini, Globulins and Cholesterol.Keywords: Sodium bicarbonate, Biochemical traits, Broiler chickens.